Development, Implementation, and Assessment of a Genetics Curriculum Across Institutions - Sarah Dotters-Katz; Ginger Hocutt; C Michael Osborne; Emily E. Hardisty; Laurie Demmer; Neeta Vora (American Journal of Perinatology Reports, 2016)
Abstract